Moderated serial mediation effects of adaptation problems, academic stress, and interpersonal relationships on the sleep quality of early-year university students - Zhao, Chenyang; Zhang, Yang (Frontiers in Public Health, 2024)
PurposeDue to heightened anxiety levels, sleep disorders become more prevalent among university students. This study, centered on adaptive capacity in early-year university students, aimed to explore the underlying mechanisms through which anxiety affects sleep quality.MethodsBetween February 2023 and June 2023, a cohort of first- and second-year university students (mean age 18.8 years) from Hunan Province, China, took part in an online survey. Anxiety was assessed using the Self-rating Anxiety Scale; adaptation problems, academic stress, and interpersonal relationships were assessed using the Adolescent Self-Rating Life Events Checklist; and sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). A moderated serial mediation model, based on Hayes’ Model 92, was used to assess the hypothesized model.ResultsThe survey resulted in 3,490 valid responses. Among respondents, 24% exhibited anxiety symptoms and 30.4% showed abnormal sleep patterns (i.e., PSQI score ≥ 8). The most significant path identified based on indirect effects was anxiety (β = 0.109), adaptation problems (β = 0.183), academic stress (β = 0.081), and sleep quality (all p-values < 0.001). Furthermore, interpersonal relationships moderated the effects of adaptation problems (β = −0.015, p < 0.001), academic stress (β = −0.012, p < 0.001), and anxiety (β = 0.003, p = 0.002) on sleep quality.ConclusionElevated anxiety and sleep disorders are common among university students. Adaptive capacity may play a crucial role in sleep disorders among early-year university students. Interventions such as fostering strong interpersonal relationships in campus environments, may prove beneficial in improving academic performance and sleep quality.